Developing speaking skills of young learners through interactive activities - Mutalliyeva, Malika (The Lingua Spectrum, 2026)
This article discusses the development of speaking skills of young learners through interactive activities in English language classes. Speaking is one of the most important and, at the same time, one of the most challenging language skills for children, as it requires vocabulary use, pronunciation, fluency, listening comprehension, confidence, and the ability to respond in real time. The analysis shows that interactive activities increase learners’ participation in the lesson, reduce anxiety, create meaningful situations for communication, and help children use English more naturally.